Kajian Paradigmatik Terhadap Konsep Diskresi Pejabat Pemerintahan di Indonesia - Pamungkas, M. Ro'i Adhi (Hukum dan Masyarakat Madani, 2020)
The concept of discretion after the enactment of the Law on Government Administration, changed from the concept of free and independent discretion to bound and procedural discretion. This study aims to find out and analyze a paradigmatic study of the concept of government officials' discretion in Indonesia. This study uses a qualitative method with a normative juridical approach and is presented in a descriptive analytical form. The concept of discretion in Indonesia in the paradigmatic study shows that there has been a shift from the meaning of discretion from the interpretivism paradigm which means that discretion is carried out freely and independently, into discretion in the postpositivism paradigm which emphasizes limited and bound discretion. The concept of discretion in Indonesia must be returned to the paradigm of interpretivism. that discretion is a free action from the government in order to realize its duty to realize the welfare of society without any complicated procedural elements full of conditions. The policy makers should return the discretion to the original understanding so that there is no government stagnation, which is contrary to the objectives of the welfare state.
Keywords: Paradigmatic; Discretion; Government Officials.